Bioinspired Nacre-like GO-based bulk with easy scale-up process and outstanding mechanical properties. (May 2020) - Jia, Huaiming; Li, Yongcun; Luan, Yunbo; Zheng, Yihao; Yang, Jinglei; Wang, Luobin; Guo, Zhangxin; Wu, Xiaodong
Highlights: GO-based nacre-like bulks were prepared by the dry-spinning and lamination strategy. These GO-based bulks had hierarchical structures at different length scale. The mechanical properties of these bio-inspired bulks were regulatable. This regulation was achieved by adjusting different hierarchical interface bonding. Abstract: Bionic structural material is a new type of high-performance material that has promising applications in the fields of aerospace, bio-medicine, etc. Herein, an investigation on the easy scale-up process and mechanical behavior of large-sized three-dimensional graphene oxide-based bioinspired nacre bulk materials with excellent mechanical properties was carried out. These bulk materials could be prepared by a lamination assembly strategy based on mass of two-dimensional graphene oxide nacre-mimetic films that fabricated by the continuous dry-spinning assembly technology. The mechanical mechanisms analysis showed that the lamination assembly process could control the interface bonding, and regulated the interface load transfer and failure models of the hierarchical structures, then optimized the combination of strength and energy absorption of the materials to meet different application requirements. These results may provide useful guidance for the efficient and controllable production of high-performance artificial nacre structure materials in application.